2019
DOI: 10.1016/j.celrep.2019.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Regulates Neuron-Glial Communications, Synaptic Transmission, and Neuropathic Pain after Chemotherapy

Abstract: The proinflammatory cytokine interleukin-17 (IL-17) is implicated in pain regulation. However, the synaptic mechanisms by which IL-17 regulates pain transmission are unknown. Here, we report that glia-produced IL-17 suppresses inhibitory synaptic transmission in the spinal cord pain circuit and drives chemotherapy-induced neuropathic pain. We find that IL-17 not only enhances excitatory postsynaptic currents (EPSCs) but also suppresses inhibitory postsynaptic synaptic currents (IPSCs) and GABAinduced currents … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 86 publications
3
86
0
Order By: Relevance
“…One study found an increase in P2X7R-dependant glutamate release from cerebrocortical synaptosomes following oxaliplatin treatment; glutamate is the major excitatory CNS neurotransmitter, and its release was eliminated by P2X7R antagonists delivered to the spinal cord (Mannelli et al, 2015). A more positive resting membrane potential and a greater frequency of firing (i.e., hyperactivity) was observed in SOM + excitatory interneurons in the outer lamina of the dorsal horn following paclitaxel treatment; experimentally blocking the IL-17 receptor reduced both hyperactivity and CIPN symptoms (Luo et al, 2019).…”
Section: Hyperactivitymentioning
confidence: 99%
“…One study found an increase in P2X7R-dependant glutamate release from cerebrocortical synaptosomes following oxaliplatin treatment; glutamate is the major excitatory CNS neurotransmitter, and its release was eliminated by P2X7R antagonists delivered to the spinal cord (Mannelli et al, 2015). A more positive resting membrane potential and a greater frequency of firing (i.e., hyperactivity) was observed in SOM + excitatory interneurons in the outer lamina of the dorsal horn following paclitaxel treatment; experimentally blocking the IL-17 receptor reduced both hyperactivity and CIPN symptoms (Luo et al, 2019).…”
Section: Hyperactivitymentioning
confidence: 99%
“…IL-17, secreted by CD4 + T cells, can induce epithelial cells and endothelial cells to synthesize IL-6, PG, and other cytokines, and combination with the TNF signaling pathway to promote inflammation [ 33 ]. Inhibition of IL-17 can effectively relieve pain and inhibit peripheral nerve sensitization [ 34 ]. C-X3-C motif chemokine ligand 1 (CX3CL1) is a kind of chemokine.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence for this is mainly based on the observed significant antiallodynic and antihyperalgesic effects of GAT-1 inhibitors in rodent models of CIPN. Decreased GABAergic neurotransmission due to excessive IL-17 levels in the spinal cord has been linked to CIPN caused by paclitaxel [171], and the inhibition of GABA reuptake with by NO-711, a selective GABA transporter isoform 1 (GAT-1) inhibitor [172], prevents the development of thermal hyperalgesia and allodynia in paclitaxel-treated mice. NO-711 is also therapeutically effective for pre-existing CIPN [173].…”
Section: Central Nervous System Structures and Neurotransmittersmentioning
confidence: 99%